Housing conditions in the Romanian rural household in the 21st century - Lorena Florentina Chiţea (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Living conditions in the rural area are precarious in Romania, our country being at the bottom of the European ranking, and the situation is getting worse as the degree of isolation increases (mainly in the hilly and mountain areas) combined with the precariousness of livelihood resources in these areas (extremely low possibilities of incomegaining employment, as well as with poor coverage of social services (education, healthcare and social assistance services, etc.). The housing conditions in the Romanian rural household reveal a series of disparities, the most obvious being the rural / urban divide, as well as the disparities existing between different rural areas. The main hypothesis of the paper is the following: there is a strong link between the housing conditions and the development level in the rural area, as well as the rurality level. From the methodological point of view, the first stage of the study was the selection of housing indicators, followed by the identification of the correlation between these indicators and the degree of rurality at county level, in the period 2007-2020. The results reveal a strongly significant correlation between the living conditions and the degree of rurality, the important cities functioning as a growth and development pole for the rural areas in their proximity, with beneficial effects on the housing conditions (modernization of dwellings and easy access to utilities).
Keywords: R00; R210; I310; 330; rural-urban divide; rural dwelling; living conditions; housing strategies